Strategic Innovative Leadership in the Food and Beverages Industries in South Africa Ask ChatGPT - Maphosa, Justice Peace (Digital Repository of Theses, 2025)
This study aims to clarify the processes of leadership for innovation, encompassing its development, creation, and characterization, by analysing the experiences, environment, and internal dynamics of an innovation climate within the organizational frameworks of SMEs in the food and beverages sector in South Africa. The quantitative deductive techniques and methodologies deployed, dissect, exhaust and examine the conventional understanding of leadership, which underpins the leader encouraging and inspiring individuals to attain a goal. The study sampling investigates the realm of individual leadership for innovation, revealing a fragmented and inadequate body of research that systematically integrates psychological factors clarifying the impact of antecedent variables on individual creativity in this study. This is empirically tested, initially at the personal-organizational level and subsequently within the industrial sector, ultimately shaping their daily innovation practices and mirroring their national culture. The study parameters look at the entire measurement model and the preliminary model findings to determine the model selection in structural equation modelling. This was thought to be appropriate in order to determine the cause of the model fit deterioration. Consequently the study looks at each path for the regression weights and finds three components that scores relatively high, namely; (a) the leader's capacity to interact with the teams and optimize revenue; (b) cultural resemblance and profit maximization; and (c) the followers' competencies and the maximization of their chances for successful growth through coaching. The validation approach includes a measurement model fit, using CFA, resulting in the reliability scores during this process varying. This thesis indicates and paints a predominantly inadequate theoretical evolution of leadership ethos and values across time, needing further research and enhancements. The study indicates that leadership influences staff innovation, leading to financial returns and enhanced organizational success. The regression weights that supplied the strength and significance of the correlations between the independent factors and the dependent variable, shows that within the observed path, innovation mediated for performance and passive behaviors regulated the cultures existent. There is a relationship between Leadership Coaching, which is found to regulate for the knowledge and experience. The Leadership moderated the innovation platforms mediated by Coaching Commitments to Followers, resulting in the performance of entities under study. The study eventually conclude that further research is essential on (1) the psychological factors clarifying the relationship between leadership and individual innovation, and (2) the contextual, organizational, and cultural components intrinsic to statehood and national power that affect leaders' ability to influence innovation within R&D teams